2011
DOI: 10.3892/ijo.2011.954
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antitumor effect of interferon-ß with gemcitabine in interferon-α-non-responsive pancreatic cancer cells

Abstract: Abstract. Interferon (IFN)-ß is reported to have more potent antitumor effects than IFN-·. The aim of this study was to compare the synergistic antitumor activity of both IFNs when combined with gemcitabine on cultured pancreatic cancer cells expressing various levels of IFN receptor. The growthinhibitory effects of IFN-· and IFN-ß in combination with gemcitabine on three human pancreatic cancer cell lines (BxPC-3, MIAPaCa-2, Panc-1) were evaluated by MTT assay and isobolographic analysis. We also correlated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Tomimaru et al . confirms this hypothesis and showed that IFN-β combined with gemcitabine was able to induce synergistically anti-tumour effects even in the pancreatic cancer cells with low IFN receptor expression [22]. Taken this together, this seems promising and further in vivo research is definitely necessary.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Tomimaru et al . confirms this hypothesis and showed that IFN-β combined with gemcitabine was able to induce synergistically anti-tumour effects even in the pancreatic cancer cells with low IFN receptor expression [22]. Taken this together, this seems promising and further in vivo research is definitely necessary.…”
Section: Discussionmentioning
confidence: 56%
“…[20, 32, 33] established a trend towards the importance of the IFN receptor in the response of IFN-α and –β; however, the number of cell lines used in these studies was very low. Furthermore, although some studies did show promising results [11, 17, 18, 22], the effect of IFN-β in the treatment of pancreatic cancer still remains underexposed. Therefore, in this study, we evaluated the type-I IFN receptor expression in a large panel of available human pancreatic cancer cell lines and associated the receptor expression with the anti-tumour potencies of IFN-α and IFN-β.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…inhibition of cell proliferation, induction of apoptosis, and cell cycle arrest. Importantly, type I IFNs have been shown to sensitize cancer cells to chemo- and radiotherapy [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%